Feminine Persuasion - Stirratt, Betsy; Johnson, Catherine (Indiana University Press, 2003)
Marking 50 years since the publication of noted sexologist Alfred Kinsey's Sexual Behavior in the Human Female, Feminine Persuasion: Art and Essays on Sexuality celebrates the diverse and multifaceted expressions of women's sexuality that have emerged since Kinsey's study heralded a new era. This beautifully illustrated book showcases five centuries of diverse visual interpretations of female sexuality collected by The Kinsey Institute, and includes work by the contemporary artists Mariette Pathy Allen, Ghada Amer, Patty Chang, Judy Chicago, Renee Cox, Judy Dater, Nancy Davidson, Nicole Eisenman, Laura Letinsky, and Frank Yamrus. In addition to more than 45 color and halftone plates, Feminine Persuasion features two scholarly essays that place this wide-ranging work in context. Assessing what the ideal body image of the original Kinsey subjects might have been, June M. Reinisch discusses the ever-changing standards of female beauty, while Jean Robertson, in a survey of the history of feminist art over the past half century, explores the complex dimensions that constitute this work. The catalog for a three-part exhibition to be presented at the Indiana University School of Fine Arts Gallery from February 14 through March 14, 2003, Feminine Persuasion reveals the future toward which Kinsey's study pointed and gives us a glimpse of the great variety of expressions in the making.